The excavation of a henge, stone circles and metal-working area at Moncrieffe, Perthshire (Proceedings of the Society of Antiquaries of Scotland, 1987)
The site was excavated in advance of roadworks on the M90 motorway. Four phases of activity were recognized.Phase 1 A class 1 henge monument with a concentric ring of nine pits within. Beaker sherds were recovered from the ditch. A cremation lay outside the entrance. Phase 2 A small burial cairn with contiguous peristalith of stones surrounded by a ring of free standing monoliths. The monument of this phase was almost completely destroyed. Phase 3 A ring of eight free standing monoliths, graded in height from SW to NE; recumbent stones lay between the three tallest monoliths on the south-west arc. At the centre a possible ring cairn was accompanied by cremated burials in pits.Phase 4 The centre of the monument was used as a metallurgical workshop for smelting iron and casting leaded bronze.